Parity and Number of Teeth in Japanese Women: Results from the Japan Nurses' Health Study - Akira Taguchi; Kazue Nagai; Yuki Ideno; Takumi Kurabayashi; Kunihiko Hayashi (Mary Ann Liebert, 2020)
Background: Parity is thought to be associated with a decreased number of teeth present in women. However, educational level and social status, which are particularly significant risk factors for loss of teeth, have been heterogeneous in previous observations. This cross-sectional survey aimed to clarify the associations of parity with the risk of having <20 teeth in Japanese female nurses participating in the Japan Nurses' Health Study (JNHS). Methods: In the third follow-up questionnaire of the JNHS, 11,299 women aged 27?82 years participated in this study. The number of participants according to age range was 7,225 (63.9%) aged <50 years and 4,074 (36.1%) aged ?50 years. Information on parity and risk factors for loss of teeth was collected through a baseline questionnaire and then a follow-up questionnaire. Multivariate logistic regression analysis was used to calculate the adjusted odds ratio (OR) and 95% confidence interval (CI) of having <20 teeth according to parity category. Results: Participants ?50 years who had experienced three or more deliveries had a significantly higher risk of having <20 teeth than those who had not experienced delivery (OR?=?1.59, 95% CI?=?1.14?2.20), although this finding was not observed in participants <50 years. In addition to parity, age and current smoking may be independent risk factors for having <20 teeth in Japanese nurses. Conclusions: Higher-parity female nurses ?50 years may be more likely to lose teeth than those who have not experienced delivery.